Skin disorders of the nipple and mammary region. - Bonifazi, E.; Cutrone, M.; Milano, A. (European Journal of Pediatric Dermatology, 2004)
The mammary region is anatomically characterized by the presence of the nipple and mammary gland tissue. The latter consists of a modified apocrine sweat gland. From a physiological point of view, this region is characterized by an enlargement in the puberal period, essentially in females. In the latter the mammary region is a secondary sexual character. From a psychological point of view, the mammary region is particularly important, also as an exposed site, mainly in females. From a dermatological point of view, the nipple is a raised site, as compared with the surrounding skin, and intensely pigmented. This is responsible for the elective localization of atopic dermatitis and vitiligo on the nipple. Moreover, the mammary region, which is sensible to the hormone stimuli, rapidly enlarges at puberty in females, due to the significantly increased mammary tissue, and also its surface significantly increases. This is responsible for a significant enlargement of the nevus lesions of this region at puberty. The miniature puberty occurring in the first weeks of age affects also the mammary region, being responsible for characteristic signs.